2021
DOI: 10.1111/hepr.13732
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of atezolizumab plus bevacizumab in patients with unresectable hepatocellular carcinoma in early clinical practice: A multicenter analysis

Abstract: Purpose: To assess the impact of clinical factors on the safety and efficacy of atezolizumab plus bevacizumab (ATZ + BV) treatment in patients with unresectable hepatocellular carcinoma (u-HCC).Method: Ninety-four u-HCC patients who were treated with ATZ + BV at multiple centers were enrolled. We defined Child-Pugh (CP)-A patients who received ATZ + BV treatment as a first line therapy as the 'meets the broad sense of the IMbrave150 criteria' group (B-IMbrave150-in, n = 46), and patients who received ATZ + BV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 31 publications
3
40
4
Order By: Relevance
“…Some previous clinical studies have reported the early experience of atezolizumab plus bevacizumab therapy as primary systemic chemotherapy for HCC, with the ORRs reportedly ranging from 31.8% to 37.5% and the DCRs reportedly ranging from 81.3% to 94.5% according to mRECIST. [14][15][16][17] The DCRs in these clinical practice studies, and the ORR and the PFS in our study were slightly better than those from the IMbrave150 trial. Most of these realworld studies had small cohorts but larger proportions of patients with BCLC stages of A or B (47.0%-68.2%) when compared with those of the IMbrave150 trial (17.9%).…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…Some previous clinical studies have reported the early experience of atezolizumab plus bevacizumab therapy as primary systemic chemotherapy for HCC, with the ORRs reportedly ranging from 31.8% to 37.5% and the DCRs reportedly ranging from 81.3% to 94.5% according to mRECIST. [14][15][16][17] The DCRs in these clinical practice studies, and the ORR and the PFS in our study were slightly better than those from the IMbrave150 trial. Most of these realworld studies had small cohorts but larger proportions of patients with BCLC stages of A or B (47.0%-68.2%) when compared with those of the IMbrave150 trial (17.9%).…”
Section: Discussioncontrasting
confidence: 60%
“…In the IMbrave150 trial, patients receiving atezolizumab plus bevacizumab had an ORR of 33.2% and a DCR of 72.3% according to mRECIST and the median PFS was 6.9 months 1,13 Similarly, in the present study, the Atezo + Beva group had an ORR of 43.8% and a DCR of 76.6% according to mRECIST, and the median PFS was 8.8 months. Some previous clinical studies have reported the early experience of atezolizumab plus bevacizumab therapy as primary systemic chemotherapy for HCC, with the ORRs reportedly ranging from 31.8% to 37.5% and the DCRs reportedly ranging from 81.3% to 94.5% according to mRECIST 14–17 . The DCRs in these clinical practice studies, and the ORR and the PFS in our study were slightly better than those from the IMbrave150 trial.…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…This difference may have been due to the small number of cases in the current study. In addition, it should be noted that previously reported NLR cut-off values for predicting patient outcomes differ between studies [15,[43][44][45], and NLRs change due to various patient conditions (e.g., infections and certain medications, particularly steroidbased immunosuppressive regimens). Therefore, more robust NLR cut-off values are desirable for use in daily clinical practice.…”
Section: Kawamura Et Almentioning
confidence: 99%
“…As in the previous reports [41,42], readministration of lenvatinib after diagnosed disease progression during immunotherapies has the potential of disease control effect in some patients. Recently, other researchers reported the utility of NLRs for predicting patient outcomes following Atezo/Bev treatment of HCC [15,[43][44][45]. Furthermore, Maesaka et al [15] reported an NLR cut-off value of ≥3 as a useful predictor for HPD.…”
Section: Kawamura Et Almentioning
confidence: 99%